Raumzeichen - Raumsymbole - lpsen, Detlev (Österreichische Zeitschrift für Geschichtswissenschaften, 2001)
Aside form the purely functional aspects of their use, architecture and urban development always constitute a form of culture as weil, in the sense that they form a system of interpretations and meanings. The simplest form of interpretation serves the purpose of orientation; the situation becomes more complex when one starts to consider the possible connotations of that interpretation. The real problem for architecture lies in the relationship between orientatory signs and symbolic indicators of meaning. How is it possible to conceive of spatial order, which is characterized by fixed denotations and connotations, but which simultaneously has to leave itself open to new interpretations and meanings? The concept of disposition does not contain within itself the logic of its own transformation, but perhaps the changeability of spatial signs and symbols can be defined more precisely through the relationship between real and virtual space.